Civilian protection in the twenty-first century : governance and responsibility in a fragmented world - Jacob, Cecilia (Oxford University Press, 2021)
There has been a significant consolidation of international norms to advance human protection objectives in current global politics. Yet, while civilian protection is at the heart of international humanitarian law and the United Nations global security agenda, armed conflicts today are increasingly fragmented. The current global security environment creates significant ethical and political complexities for the actors operating in this field to protect civilians. This volume interrogates the diversity of practices and the politics of civilian protection at the individual and community as well as the state, non-state, and the international community levels to conceptualize civilian protection in this complex environment. The book comprises thematic chapters on humanitarian intervention, protection of populations of concern including refugees and internally displaced persons (IDPs), and international diplomacy, which are enriched with six case studies from Asia and Africa. Combining conceptual debate with empirical evidence, the contributors describe the contexts in which interventions occur and the practical ways in which protection mechanisms have been implemented. This volume offers alternatives that can be adopted to improve and build upon current practices of civilian protection.